2000
DOI: 10.2174/0929867003375281
|View full text |Cite
|
Sign up to set email alerts
|

Huperzine A, A Potential Therapeutic Agent for Treatment of Alzheimer's Disease

Abstract: HupA is a potent, reversible and selective inhibitor of AChE with a rapid absorption and penetration into the brain in animal tests. It exhibits memory-enhancing activities in animal and clinical trials. Compared to tacrine and donepezil, HupA possesses a longer duration of action and higher therapeutic index, and the peripheral cholinergic side effects are minimal at therapeutic doses. This review article deals with a comprehensive survey of the progress in chemical and pharmacological studies of HupA includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
81
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(82 citation statements)
references
References 50 publications
0
81
0
1
Order By: Relevance
“…33 In addition to the Food and Drug Administration-approved AChE-Is, several other such inhibitors at various stages of research and development have been reported. These include compounds such as: phenserine, 34,35 CHF2819, 36 TAK147, 37 TV3326, 38 huperzine A and analogs, 39 NP-61, 40 and Memoquin. 41 Preclinical studies showed that some of these newer AChE-Is may have additional properties versus the existent AChE-Is prescribed drugs that may enhance their putative therapeutic value in AD treatment.…”
Section: Ache-ismentioning
confidence: 99%
“…33 In addition to the Food and Drug Administration-approved AChE-Is, several other such inhibitors at various stages of research and development have been reported. These include compounds such as: phenserine, 34,35 CHF2819, 36 TAK147, 37 TV3326, 38 huperzine A and analogs, 39 NP-61, 40 and Memoquin. 41 Preclinical studies showed that some of these newer AChE-Is may have additional properties versus the existent AChE-Is prescribed drugs that may enhance their putative therapeutic value in AD treatment.…”
Section: Ache-ismentioning
confidence: 99%
“…It has been shown to contain an extract Huperzine A (HupA). It is known to be a selective inhibitor of acetylcholine esterase with significant pharmacodynamics and kinetic properties in the brain demonstrated in animal studies [65]. It has long half-life and tolerance with few cholinergic side effects [65].…”
Section: Potential Phytopharmacological Management Of Alzheimer's Dismentioning
confidence: 99%
“…However, the order of the binding energies was the same as that expected on the basis of the experimental values of IC 50 . [83] a Experimental values of IC 50 are informed in M. These values were determined according to the Ellman method, [50] with some modifications, as described in the experimental section.…”
Section: Ache-11b () and Ache-2 ()mentioning
confidence: 99%